Occurrence and survival of enteric viral indicators in sediments in tropical aquatic ecosystems - Anuja Padma Gopalakrishnan (2017)
The current water quality guidelines intended to protect people from gastrointestinal disease resulting from the recreational use of water bodies solely rely on counts of indicator bacteria in the water phase. However previous studies have indicated that sediments in aquatic bodies could harbour pathogenic microorganisms. Sediments could deteriorate the water quality if there is sediment resuspension into overlying water column in an aquatic body. Compared to water, little is known about microbial quality of sediments in aquatic environment. Potential risks associated with sediment resuspension to recreational users is not well studied. Hence, determining the microbial quality of sediments in the water bodies is important. In this thesis, microbial quality of sediments in two aquatic bodies WB1 and WB2 was investigated. WB1 and WB2 are two important urban water bodies serving as sources of potable water. Currently WB2 is open to public for various non-swimming water recreation activities such as boating, canoeing and kayaking. In future, authorities may open WB1 for recreational purposes as part of Active beautiful clean (ABC) waters programme initiated by Public Utilities Board (PUB) of Singapore. WB1 and WB2 have different land use type. The microbial quality investigation in the present study focussed on the (i) occurrence of conventional bacterial indicators (E.coli and enterococci) and potential enteric viral indicators (FRNA coliphages) in the sediments of WB1 and WB2 and (ii) Survival and adsorption of enteric viral indicators in tropical sediments (sediments of WB1 and WB2 as well as a marine clay sediment). As there is no microbial guideline requirement of permissible levels for indicator bacteria in sediments for recreational purposes, a quantitative microbial risk assessment (QMRA) was done. Quantitative microbial risk assessment based on the enterococci concentration showed that the maximum single event risk for WB1 was within the USEPA (United States Environmental Protection Agency) acceptable freshwater illness rate of 3.6%. In WB2, even though there was a very low probability (0.012) that the maximum risk was above the guideline requirement, 98.8% of the time the risk was below the guideline requirement. F-specific RNA coliphages (FRNA) are potential candidates of human enteric viruses responsible for gastroenteritis illness. However, information regarding the genetic diversity and distribution of these phages in sediments, especially from a tropical climate is not available. Since the concentration of FRNA phages in the sediments of WB1 and WB2 was low, enrichment method (USEPA method 1601) was necessary to detect FRNA phages. Molecular techniques were used to detect and characterise the FRNA phages from the aquatic sediment samples. The two-step enrichment method coupled with quantitative PCR (qPCR) used in this study was shown to be a reliable method for genotyping FRNA coliphages, especially when concentrations of phages are low in the environmental samples. Genotyping of FRNA coliphages has been used to differentiate between animal and human faecal pollution. Genogroups II and III are typically associated with human excreta and genogroups I and IV with animal faeces. In the present study, G II was the most prevalent group with a detection rate of 29% followed by GI (19%) and GIII (16%). Genotype IV was not detected in any of the samples. The low indicator virus titre observed in the sediments of WB1 and WB2, led to the survival and adsorption study of two model viruses (MS2 and phiX174) in tropical sediment suspensions using laboratory microcosms. The effect of electrostatic and hydrophobic forces in viral adsorption to sediments was assessed through adsorption data analysis. In addition, it was found that presence of indigenous microbes had an obvious effect on virus survival in sediments. There are some previous studies indicating that sediments have protective effect on virus survival by which sediment associated viruses are protected from inactivation. In this study the protective effect of sediments for the virus survival was not observed.